INSTINCT, CONSCIOUSNESS, LIFE: ruyer contra bergson. Issue 5 (3rd September 2019) - Ruyer, Raymond; Posteraro, Tano S.; Roffe, Jon
Abstract: The question of Ruyer's relationship to Bergson remains under-theorized. This article attempts to address that problem by introducing a little-known essay written by Ruyer on the topic of Bergson's theory of vital sympathy, "Bergson et le Sphex ammophile, " which appeared in 1959, one year after the publication of La Genèse des formes vivantes and the completion of Ruyer's systematic philosophy of biology. An English translation of the essay appears below. In order to introduce it, we begin by presenting a brief account of Ruyer's philosophy of biology. Then we reconstruct Ruyer's early critical engagement with Bergson, and finally we investigate some occluded points of overlap between the two. We suggest that Ruyer's early critique of Bergson's theory of perception may have made it difficult for him to appreciate what the two had in common. Their commonalities and differences form part of the subject matter of the translated essay.